2021
DOI: 10.3389/fpsyt.2021.673805
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Criticism Modulates Left but Not Right Amygdala Functional Connectivity in Healthy Adolescents: Individual Influences of Perceived and Self-Criticism

Abstract: Background: Frequent exposure to criticism is a known risk factor for various adult psychiatric disorders. Adolescents may be even more vulnerable to (parental) criticism, as their imbalanced brain maturation makes them prone to stronger mood changes and less effective emotional regulation. Identifying which adolescent subgroups are more vulnerable than others could be of great clinical relevance. Perceived criticism (PC) and self-criticism (SC), two related but distinct traits, could well be crucial vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…People may feel controlled by others' demands and expectations and be preoccupied with concerns about appearing inadequate and making mistakes (Hewitt et al, 2017). Apprehending others' perceptions of the self as critical or judgmental can hyperactivate the perception of negative emotions with defensive functions (e.g., fear, anxiety) and hypoactivate the capacity to regulate and mentalize these very emotions (Bonduelle et al, 2021;Kim et al, 2020;Petrocchi and Cheli, 2019). Socially prescribed perfectionism is associated with higher levels of psychopathology and psychological distress in both clinical and nonclinical samples (Jahromi et al, 2012;Smith et al, 2018aSmith et al, , 2018b.…”
Section: Psychoticism Threatening Beliefs and Psychological Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…People may feel controlled by others' demands and expectations and be preoccupied with concerns about appearing inadequate and making mistakes (Hewitt et al, 2017). Apprehending others' perceptions of the self as critical or judgmental can hyperactivate the perception of negative emotions with defensive functions (e.g., fear, anxiety) and hypoactivate the capacity to regulate and mentalize these very emotions (Bonduelle et al, 2021;Kim et al, 2020;Petrocchi and Cheli, 2019). Socially prescribed perfectionism is associated with higher levels of psychopathology and psychological distress in both clinical and nonclinical samples (Jahromi et al, 2012;Smith et al, 2018aSmith et al, , 2018b.…”
Section: Psychoticism Threatening Beliefs and Psychological Distressmentioning
confidence: 99%
“…Self-critical people tend to perceive interpersonal experiences in a way that focuses on personal inadequacies and shame and to see others as judgmental (Gilbert et al, 2006). When coupled with a tendency for social cognitive distortion, self-criticism may activate threat responses, fueling distress and diminishing the capacity for self-soothing (Bonduelle et al, 2021; Cheli et al, 2021; Gilbert and Mascaro, 2017; Gumley et al, 2010; Petrocchi and Cheli, 2019). From an evolutionary point of view, self-criticism is not maladaptive per se, but may be considered a distinctive and potentially threatening process for individuals functioning within our hyperaffiliative species.…”
Section: Psychoticism Threatening Beliefs and Psychological Distressmentioning
confidence: 99%
“…On the other hand, vACC and vmPFC activity are more consistently observed during implicit regulation (Etkin et al, 2010;Quirk et al, 2006;Sotres-Bayon & Quirk, 2010). A recent study also found that after criticism, functional connectivity between the left amygdala with brain regions related to sustained emotional processingspecifically, the left putamen, left mediofrontal orbital cortex, left precuneus and right precentral gyrusincreases (Bonduelle et al, 2021). Increased functional connectivity between the amygdala and the left putamen occurs after inducing stress, which indicates a shift towards more habitual behaviour under stress (Chang & Yu, 2018).…”
Section: Neuroimaging Studies On Criticism and Perceived Criticismmentioning
confidence: 94%
“…In addition, functional connectivity between regions were also found to be associated with perceived criticism. In the study by Bonduelle et al (2021), perceived criticism scores were correlated with the increase in functional connectivity between the left amygdala and the left superior parietal cortex and the left precuneus. The left superior parietal cortex also shows functional connections with areas involved in emotion regulation (Kohn et al, 2014) whereas the left precuneus shows increased activation during self-referential processing (Molnar-Szakacs et al, 2013) and ruminative thinking (Burkhouse et al, 2017).…”
Section: Neuroimaging Studies On Criticism and Perceived Criticismmentioning
confidence: 97%